Research trends on endoscopic mucosal resection: A bibliometric analysis from 1991 to 2021 - Yang, Yihan; Xu, Xuan; Wang, Menghui; Zhang, Yang; Zhou, Pinglang; Yang, Sifan; Shu, Xu; Xie, Chuan (Frontiers in Surgery, 2022)
Background: In recent years, the rapid development of digestive endoscopy technology has brought revolutionary changes to endoscopic therapy. A growing number of articles have been published annually. We aimed to explore global scientific outputs and hotspots of endoscopic mucosal resection (EMR) published by different countries, organizations, and authors. Methods: We extracted relevant publications from the Web of Science Core Collection (WOSCC) on June 23, 2022. We examined the retrieved data by bibliometric analysis (e.g., cocited and cluster analysis, keyword co-occurrence) using the software CiteSpace and VOSviewer to analyze and predict the trends and hot spots in this field. Results: A total of 2,695 papers were finally identified. The results showed that the number of articles fluctuated with the year and reached its peak in 2021. NATIONAL CANCER CENTER JAPAN was the most influential institution. MICHAEL J BOURKE and YUTAKA SAITO are two of the most prolific scholars. ENDOSCOPY and GASTROINTESTINAL ENDOSCOPY were the most productive journals. “Early gastric cancer” and “Barrett's esophagus” were the focus of EMR research. "Adverse events", "cold snare polypectomy" and "outcomes" have become increasingly popular in recent years and could become hot spots in the future. Conclusion: In this study, we summarized the characteristics of the publications; identified the most influential countries, institutions, and journals; and identified the leading topics in the EMR field.